Keratins 8 and 18 are type II acute‐phase responsive genes overexpressed in human liver disease. (26th June 2014) - Guldiken, Nurdan; Usachov, Valentyn; Levada, Kateryna; Trautwein, Christian; Ziol, Marianne; Nahon, Pierre; Strnad, Pavel
Abstract Background & Aims Keratins (Ks) 7, 8, 18 and 19 constitute important markers and modifiers of liver disease. In mice, K8 and K18 are stress inducible and a dysregulated K8 > K18 stoichiometry predisposes to formation of Mallory–Denk bodies (MDBs), i.e. aggregates characteristic of chronic liver disorders such as alcoholic liver disease (ALD). In our study, we analyse the expression and the regulation of keratins in context of human liver disease. Methods K7, K8, K18 and K19 mRNA levels were determined in liver biopsies from patients with ALD, non‐alcoholic steatohepatitis (NASH), chronic hepatitis B (HBV), hepatitis C (HCV) and from control subjects. HepG2 and Hep3B cells were treated with IL‐1β, IL‐6 and TNF‐α. Mice were injected with turpentine, an established IL‐6 inducer. Results K7, K8 and K18 were 1.5‐ to 3‐fold upregulated in livers of ALD and HCV patients with a more active disease, but not in HBV/NASH subjects, while K19 was significantly elevated in all analysed disorders. K8 and K18 expression displayed a strong correlation (r = 0.89), but dysregulated levels with the K8 > K18 state were seen in ALD. All keratins were overexpressed in subjects with moderate vs. minimal inflammation, while K7, K8 and K18 were upregulated in patients with advanced liver fibrosis. In HepG2/Hep3B cells, IL‐6 treatment but not IL‐1β or TNF‐α significantly increased K8 and K18 expression and elevated K18 levels were seen after turpentine injection. Conclusions Keratins represent type II acute‐phase responsive genes overexpressed in specific human liver disorders. A K8 > K18 state occurs in ALD and predisposes to MDB formation.